Growth Inhibition of Streptococcus mutans by Fluoride Varnish Containing Averrhoa bilimbi L. and Piper crocatum Leaves Extracts - Hermansyah, Heri; Gabriella, Maria; Eriwati, Yosi Kusuma (Applied mechanics and materials, 2022)
Fluoride varnish is commonly used as topical fluoride therapy to prevent dental caries. Dental caries is a dissolution of tooth surface caused by the metabolic activity of Streptococcus mutans in the presence of carbohydrates. Fluoride varnishes containing antibacterial agents significantly affect the inhibition zone of Streptococcus mutans. Prior studies also note the inhibitory effect of wuluh starfruit (Averrhoa bilimbi L.) leaves extracts and fast release fluoride varnish containing red betel (Piper crocatum) leaves extracts on Streptococcus mutans. The purpose of this study was to evaluate the antibacterial effect of adding wuluh starfruit leaves extracts, and red betel leaves extracts to a formulation of fluoride varnish on the growth inhibition of Streptococcus mutans, the fluoride ion release, and the pH obtained from the fluoride varnish. The concentration of antibacterial extracts used was 0.1 g/mL each and MI Varnish served as control. The growth inhibition zone of Streptococcus mutans was measured using disk-diffusion agar method with 3 repetitions. The data produced were analyzed using the Kruskal-Wallis and Mann-Whitney U-tests. Fluoride varnishes containing antibacterial agents used in this study resulted in greater inhibition zone of Streptococcus mutans than control (P < 0.05). The addition of red betel leaves extracts resulted in greater mean diameter of inhibition zone (14.22 mm) than that of wuluh starfruit leaves extracts (13.75 mm), but there was no significant difference (P > 0.05). The fluoride ion release of fluoride varnish containing red betel leaves extracts and wuluh starfruit leaves extracts after 360 minutes is 269.08 mg/L and 229.32 mg/L, respectively. The pH of both fluoride varnishes is above the critical pH of hydroxyapatite. Thus, wuluh starfruit leaves extracts, and red betel leaves extracts have the potential to be used as one of the ingredients in the formulation of fluoride varnish to achieve better growth inhibition of Streptococcus mutans.